2019
DOI: 10.1111/jog.13953
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of bidet toilet use: Association of abnormal vaginal colonization and preterm birth in high‐risk pregnant women

Abstract: Aim This study aimed to evaluate the association of bidet toilet use with abnormal vaginal microbial colonization and preterm birth (PTB) in high‐risk pregnancies. Methods This is a prospective cohort study of 208 women, who were admitted to a high‐risk pregnancy unit, due to preterm labor, preterm premature rupture of the membrane, or short cervical length, in two tertiary hospitals from April 2015 to July 2017. Responses to a questionnaire about using bidet toilet and vaginal culture were obtained upon admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Beside the effect of bidet toilet use in relieving constipation, studies also report that the use of these toilets in public areas has some risks, and that the water nozzles of bidet toilets are contaminated with a wide range of bacteria, especially in hospitals, making them a potential vehicle for cross-infection. 20,21 Kim et al conducted a study of high-risk pregnant women with preterm labor and reported that the use of a bidet toilet was associated with abnormal vaginal colonization and increased the rate of preterm labor in high-risk pregnancies. 21 Ogino et al conducted a study with 268 non-pregnant women of reproductive age and reported that habitual use of bidet toilets aggravated vaginal microflora, either by depriving normal microflora or facilitating opportunistic infection of fecal bacteria and other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the effect of bidet toilet use in relieving constipation, studies also report that the use of these toilets in public areas has some risks, and that the water nozzles of bidet toilets are contaminated with a wide range of bacteria, especially in hospitals, making them a potential vehicle for cross-infection. 20,21 Kim et al conducted a study of high-risk pregnant women with preterm labor and reported that the use of a bidet toilet was associated with abnormal vaginal colonization and increased the rate of preterm labor in high-risk pregnancies. 21 Ogino et al conducted a study with 268 non-pregnant women of reproductive age and reported that habitual use of bidet toilets aggravated vaginal microflora, either by depriving normal microflora or facilitating opportunistic infection of fecal bacteria and other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Kim et al conducted a study of high-risk pregnant women with preterm labor and reported that the use of a bidet toilet was associated with abnormal vaginal colonization and increased the rate of preterm labor in high-risk pregnancies. 21 Ogino et al conducted a study with 268 non-pregnant women of reproductive age and reported that habitual use of bidet toilets aggravated vaginal microflora, either by depriving normal microflora or facilitating opportunistic infection of fecal bacteria and other microorganisms. 22 Unlike these studies, Asakura et al examined the effect of bidet toilet use on preterm birth and vaginal flora in pregnant women with the participation of 2545 women who gave birth between 2006 and 2010 in Tokyo and reported that normal use of the bidet toilet by pregnant women posed no clinical health risk for preterm birth and bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the changes from baseline to 6 and 12 weeks between the placebo and MED-01 groups were analyzed using a two-sample t -test or Wilcoxon rank sum test. Additionally, an analysis of covariance was conducted with the variables bidet or tampon use and amount of smoking and frequency of intercourse [ 20 , 21 , 22 , 23 , 24 ]. The data are presented as mean ± standard deviation (SD), and the significance of the differences was verified using a two-sided test at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study has shown habitual BTS usage is associated with a high incidence of abnormal vaginal colonization by gram-negative bacteria and preterm birth in high-risk pregnancies (Kim et al, 2019) . Frequent BTS usage was related to anal itching in community-dwelling Japanese people (Tsunoda et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%